2011
DOI: 10.1287/isre.1090.0260
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Online Privacy Information on Purchasing Behavior: An Experimental Study

Abstract: While most people claim to be very concerned about their privacy, they do not consistently take actions to protect it. Web retailers detail their information practices in their privacy policies, but most of the time this information remains invisible to consumers. This paper reports on research undertaken to determine whether a more prominent display of privacy information will cause consumers to incorporate privacy considerations into their online purchasing decisions. We designed an experiment in which a sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
361
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 667 publications
(379 citation statements)
references
References 49 publications
9
361
2
7
Order By: Relevance
“…A large number of studies in recent years support this logic. Scholars have noted the growing prevalence of privacy concerns amongst consumers (Goldfarb and Tucker 2012), and have demonstrated the positive effects of privacy assurances, policies and seals on user information sharing and product purchase (Hui et al 2007;Tsai et al 2011). At the same time, a number of studies have demonstrated the value of social recognition and reputational gains as drivers of user contributions to online communities (Wasko and Faraj 2005;Zhang and Zhu 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies in recent years support this logic. Scholars have noted the growing prevalence of privacy concerns amongst consumers (Goldfarb and Tucker 2012), and have demonstrated the positive effects of privacy assurances, policies and seals on user information sharing and product purchase (Hui et al 2007;Tsai et al 2011). At the same time, a number of studies have demonstrated the value of social recognition and reputational gains as drivers of user contributions to online communities (Wasko and Faraj 2005;Zhang and Zhu 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, other research shows that people appreciate that a website is concerned about their privacy. People buy more often and more expensive goods from web sites that publicly declare that they care about protecting the privacy of their customers (e.g., see [29]). Besides, it has been proved that usable privacy policies foment trust [30].…”
Section: Discussionmentioning
confidence: 99%
“…In such transactions, customer information generally is one of the transferred business assets." An ostensible reason for firms to acquire customer records is to predict consumer preferences or offer customized services (Garfinkel et al, 2007;Li et al, 2011;Tsai et al, 2011). Our analysis suggests they may use such records simply for static price discrimination (Taylor, 2004;Fudenberg and Villas-Boas, 2006).…”
Section: H L} If and Only Ifmentioning
confidence: 91%